CLINICAL VALUE OF 4D-SPECT/CT IN PATIENTS WITH PAINFUL TOTAL KNEE ARTHROPLASTY. Issue 10 (10th June 2013) - Testa, Enrique Adrian; Rasch, Helmut; Forrer, Flavio; Hirschmann, Michael Tobias
Abstract : Twenty to forty percent of patients after primary total knee arthroplasty (TKA) are not satisfied. A considerable number report persistent or recurrent pain. As most common causes infection, aseptic loosening, instability, malposition of the TKA, arthrofibrosis and patellofemoral problems have been reported. However, in many cases after TKA the cause for the patient's problems cannot be identified unambiguously. The current clinical and radiological diagnostics including radiographs, CT, MRI, scintigraphy, SPECT or PET/CT fail to accurately establish the correct diagnosis. Recently we have highlighted the clinical value of SPECT/CT as diagnostic tool in patients with problems after TKA. We reported near perfect inter- and intra-observer reliability for their proposed standardized, easily applicable and reliable SPECT/CT algorithm including a localization scheme, intensity value and 3D prosthetic component analysis. With this specific algorithm the authors aim to identify typical distribution patterns and intensity thresholds of SPECT/CT tracer uptake, which reflect pathologies such as mechanical loosening, instability, component malposition or patellofemoral problems. The primary purpose of the present study is to evaluate the clinical value of the proposed 4D SPECT/CT algorithm including a localization scheme, intensity value evaluation and 3D analysis of TKA component position. The 4th dimension is the assessment of component position in 3D CT in relation to the mechanical axis. The secondary aim is to identify typical pattern of tracer uptake distribution and intensity values in unhappy patients after TKA and relate those to specific pathologies. One hundred unhappy patients after TKA are prospectively included. 99mTc-HDP-SPECT/CT is performed as part of the diagnostic algorithm using our previously validated protocol, which includes for the CT 3 mm slices of the hip joint, 0.75 mm slices of the knee and 3 mm slices of the ankle joint. SPECT/CT tracer uptake is localised using a specific localisation scheme, which divides the knee joint in anatomical and biomechanical regions of interest. Quantitative volumetric 3D analysis of tracer uptake intensity is performed using a customised validated software. In addition, the fermoral and tibial TKA component position (flexion-extension, varus-valgus, internal rotation-external rotation) as tibiofemoral angle is measured using another customised and validated software. The above findings is correlated with the type and design of TKA, the time from primary TKA, cemented or non cemented approach and intraoperative findings at revision surgery (loose vs well fixed TKA). With the intended results of the study we aim for a better understanding of unhappy knee joints after TKA and an improved diagnostics in a challenging group of patients. Our approach is entirely novel as it combines biomechanical data such as leg alignment and TKA component position as well as information on the bony remodelling, which is inherent in the SPECT information.